Influence of assistive technology applications on dyslexic students: The case of Saudi Arabia during the COVID-19 pandemic - Al-Dokhny, Amany Ahmed; Bukhamseen, Amani Mohammed; Drwish, Amr Mohammed (Education and information technologies, 2022)
In Saudi Arabia, the COVID-19 pandemic forced students with dyslexia to complete their learning through online applications, like their peers without dyslexia. This study explores the influence of assistive technology (AT) on improving the visual perception (VP) and phonological processing (PhP) abilities of students with dyslexia. Three learning applications were used (Google Classroom, Zoom, and Quizlet) as AT platforms. A quantitative approach was adopted based on a quasi-experimental design. Single-subject experimental methods were used to examine the influence of AT on improving students’ VP, PhP, and frequency of access (FA). Fourteen students with dyslexia who were selected as participants through purposeful sampling were divided into two experimental groups based on gender. The results showed that AT influenced the VP, PhP, and FA in both experimental groups. Girls scored higher than boys in VP, PhP, and FA, and a positive correlation was found between VP and PhP with AT applications among girls and boys. A simple linear regression analysis showed that a significant and positive relationship exists between FA and the VP and PhP abilities of students with dyslexia through AT applications.